The magnitude of gender-based violence, health consequences, and associated factors among women living in post-war woredas of North Shewa zone, Amhara, Ethiopia, 2022 - Asefa, Eyosiyas Yeshialem; Haile, Assalif Beyene; Mohamed, Osman Yimer; Berhanu, Dagimawit (Frontiers in Global Women's Health, 2024)
Background Gender-based violence (GBV) is a pervasive global public health concern and a violation of human rights, particularly pronounced in conflict settings where it is often used as a tool of warfare to instill fear and control populations. Objective Assessment of Magnitude, Associated Factors, and Health Consequences of GBV among women living in war-affected woredas of North Shewa zone, Ethiopia, 2022 Methods A community-based cross-sectional study was conducted, involving 845 randomly selected women living in conflict zones. Data on GBV experiences over the previous 3 months were collected through interviewer-administered questionnaires developed from literature review. The collected data underwent validation, entry into EPI data, and analysis using SPSS. Findings are summarized using descriptive statistics, AOR and 95% confidence interval. Result The magnitude of GBV in this study was (490, 58.0%) where, (466, 55.0%) psychological violence, (254, 30.1%) physical violence, and (135, 16.0%) reported sexual violence. A majority of the physical violence, (161, 63.4%), occurred during conflict period, with (143, 56.3%) of these cases involving armed forces, and (161, 63.4%) women experiencing physical violence in their homes. Urban Residence AOR = 2.65, CI, (1.82–3.89), Educational status of Secondary education AOR = 0.33, CI, (0.19–0.57, and ≥College AOR = 0.17, CI, (0.09–0.35), Occupation of Housewife AOR = 1.88, CI, (1.20–2.94), Private employee AOR = 6.95, CI, (3.70–13.04), Gov't employee AOR = 5.80, CI, (2.92–11.50), and others (Students) AOR = 3.46, CI, (1.98–6.01), Ever had sexual intercourse AOR = 0.46, CI, (0.25–0.83), Have heard about SRH AOR = 0.59, CI, (0.40–0.89), Have had previous GBV exposure AOR = 0.24, CI, (0.15–0.38), having a previous history of sexual violence AOR = 0.30, CI, (0.16–0.57), and Number of sexual partner AOR = 1.84, CI, (1.13–2.99) were identified to be associated factors of GBV in our study area. The most commonly reported consequences of GBV were Anxiety, depression, physical injuries, self-blame, women had school dropout, and abortion. Conclusion The study reveals a higher prevalence of GBV, resulting in profound physical, social, mental, and reproductive health challenges for survivors. To address this, multi-sectoral cooperation is advised to enhance women's empowerment, access to information, and psycho-social support in affected areas. Furthermore, national policymakers are urged to implement preventive measures during conflict and establish legal mechanisms to ensure accountability for perpetrators.